Keabsahan Pembatalan Lelang Eksekusi Hak Tanggungan Terhadap Harta Bersama - Annisya Chaerani, Putri; Thoriq Aljaad, Muhammad; Julian Theis, Gerald; Rizki Hasbi, Chintia (LPPM Universitas Ekasakti Padang, 2024)
The regulation concerning auctions in Indonesia, particularly in the context of the execution of joint property encumbrance rights, has become a crucial topic of discussion. Since the era of Dutch East Indies, auctions have been formally regulated through the Auction Regulation, still in effect based on the 1945 Constitution of the Republic of Indonesia. Despite the established auction processes, cancellations often occur due to legal violations. These cancellations can be initiated by the seller or the judiciary. The aim of this research is to examine the legal issues regarding the validity of canceling auctions in the execution of joint property encumbrance rights. The research adopts a legal research methodology utilizing legislative, conceptual, and case study approaches. The study meticulously elaborates on the procedures and legal issues related to auction cancellations, as well as the application of asset settlement in cases of joint property litigation. By highlighting various types of execution auctions and the legal aspects involved, this research delves into the processes associated with auction cancellations and their consequences. In the execution of joint property encumbrance rights, auctions do not require the consent of the husband or wife but can be annulled if it is proven that there is an unlawful act in the execution of credit agreements or the granting of encumbrance rights. Consequently, auction results can be invalidated due to the commission of an unlawful act by either party.